Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to prove a something regarding Chebyshev polynomials. Given the polynomials $T_n(x), n = 0, 1, \ldots$ which are recursively defined by $$\begin{cases} T_0(x) = 1\\ T_1(x) = x \\T_n(x) = 2x T_{n−1}(x) − T_{n−2}(x), & \text{for } n \geq 2\end{cases}$$

I want to show that

For every $n$, $$T_n(x) = \cos(n \arccos(x))$$

Is there some type of proof I could use or is just plugging in values the only way?

share|cite|improve this question
Show that $\cos (n \arccos (x))$ satisfies the recursive definition. – Qiaochu Yuan Sep 10 '12 at 1:43
So do I set it equal to the recursive definition? – Samuel Gregory Sep 10 '12 at 1:47
No, you show that it satisfies the recursive definition. In other words, set $P_n(x) = \cos (n \arccos x)$ and show that $P_0(x) = 1, P_1(x) = x, P_n(x) = 2x P_{n-1}(x) - P_{n-2}(x)$. By induction, it then follows that $T_n(x) = P_n(x)$. (You already need induction to show that a recursive definition is actually a definition of anything so this should not be too surprising.) – Qiaochu Yuan Sep 10 '12 at 1:48
Should that be P(n-2)? – Samuel Gregory Sep 10 '12 at 1:53
Yes, sorry about that. – Qiaochu Yuan Sep 10 '12 at 1:54
up vote 5 down vote accepted

Plugging in values will only prove finitely many instances.

This is a sequence of trigonometric identities. Since it's a definition by recursion, you do the proof by mathematical induction. It's obviously true if $n=0$ or $1$. So suppose it's true in the first $n$ cases, so you know $$ T_n(\cos\theta) = \cos(n\theta). $$ and similarly for $n-1$.

You want to prove $$ T_{n+1}(\cos\theta) = \cos((n+1)\theta). $$

So write $$ \begin{align} T_{n+1}(\cos\theta) & = 2(\cos\theta) T_n(\cos\theta) - T_{n-1}(\cos\theta) \\[8pt] & = 2(\cos\theta)(\cos(n\theta)) - \cos((n-1)\theta) \\[8pt] & = 2(\cos\theta)(\cos(n\theta)) - \Big( \cos(n\theta)\cos\theta + \sin(n\theta)\sin\theta \Big) \\[8pt] & = (\cos\theta)(\cos(n\theta)) -\sin(n\theta)\sin\theta \\[8pt] & = \cos((n+1)\theta). \end{align} $$

(Of course, you have to remember some basic trigonometric identities to follow this.)

share|cite|improve this answer
I was able to follow, thank you! – Samuel Gregory Sep 10 '12 at 2:52
Shouldnt it be Tn(theta) and not cos(theta)? – Samuel Gregory Sep 10 '12 at 3:13
@SamuelGregory : No, the argument above won't work in that case. Just let $x=\cos\theta$, so $\theta=\arccos x$ and $T_n(x)=T_n(\cos\theta)$. – Michael Hardy Sep 10 '12 at 17:11

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.